A Frameless Stereotactic Implantation Technique for Depth Electrodes in Refractory Epilepsy Using Intraoperative Magnetic Resonance Imaging - Roessler, Karl; Sommer, Bjoern; Merkel, Andreas; Rampp, Stefan; Gollwitzer, Stephanie; Hamer, Hajo; Buchfelder, Michael (World Neurosurgery, 2016)
Various complex techniques for depth electrode insertion in refractory epilepsy using preoperative imaging have been investigated. We evaluated a simple, accurate, cost-effective, and timesaving method using intraoperative magnetic resonance imaging (MRI).A neuronavigation-guided insertion tube attached to bone facilitated the placement of stereotactic percutaneous drill holes, bolt implantation, and frameless stereotactic insertion of depth electrodes. Image registration was carried out by head coil fiducials with trajectory planning and intraoperative electrode correction.In 6 patients with refractory epilepsy (3 women and 3 men; mean age, 30.0 years; range, 20-37 years), 58 depth electrodes (9-11 per patient) were placed. The mean length of the inserted electrodes was 37.3 mm ± 8.8 (mean ± SD) (range, 22.1-84.4 mm). The overall target point accuracy was 3.2 mm ± 2.2 (range, 0-8.6 mm), which was significantly different from the overall entry point accuracy of 1.4 mm ± 1.2 (P < 0.0001). All electrodes functioned perfectly, enabling high-quality stereo-electroencephalography recordings over a period of 7.3 days ± 0.5 (range, 7-8 days). The mean implantation time for 9-11 electrodes per patient was 115 minutes ± 36.3 (range, 75-160 minutes; 12 minutes for 1 electrode on average) including the intraoperative MRI (T1 three-dimensional magnetization-prepared rapid acquisition gradient echo, T2, and diffusion tensor imaging). There was no hemorrhage, infection, or neurologic deficit related to the procedure.Our frameless technique of depth electrode insertion using intraoperative MRI guidance is an accurate, reliable, cost-effective, and timesaving method for stereo-electroencephalography.
EVALuna2:22491

A new functional classification system (FGA/B) with prognostic value for glioma patients - Friedlein, Katharina; Bozhkov, Yavor; Hore, Nirjhar; Merkel, Andreas; Sommer, Bjoern; Brandner, Sebastian; Buchfelder, Michael; Savaskan, Nicolai E.; Eyüpoglu, Ilker Yasin (Scientific Reports, 2015)
Despite advances in multimodal treatments, malignant gliomas remain characterized by a short survival time. Surgical treatment is accepted to be the first line of therapy, with recent studies revealing that maximal possible tumor reduction exerts significant impact on patient outcome. Consideration of tumor localization in relation to functionally eloquent brain areas has been gaining increasing importance. Despite existing assessment methods, the availability of a simple but reliable preoperative grading based on functional data would therefore prove to be indispensable for the prediction of postoperative outcome and hence for overall survival in glioma patients. We performed a clinical investigation comprising 322 patients with gliomas and developed a novel classification system of preoperative tumor status, which considers tumor operability based on two graduations (Friedlein Grading - FG): FGA with lesions at safe distance to eloquent regions which can be completely resected, and FGB referring to tumors which can only be partially resected or biopsied. Investigation of outcome revealed that FGA were characterized by a significantly longer overall survival time compared to FGB. We offer the opportunity to classify brain tumors in a dependable and reproducible manner. The FGA/B grading method provides high prognostic value with respect to overall survival time in relation to the extent of location-dependent tumor resection.
EVALuna2:22845

Early postoperative tumor progression predicts clinical outcome in glioblastoma-implication for clinical trials - Merkel, Andreas; Soeldner, Dorothea; Wendl, Christina; Urkan, Dilek; Kuramatsu, Joji; Seliger, Corinna; Proescholdt, Martin; Eyupoglu, Ilker Y.; Hau, Peter; Uhl, Martin (Journal of Neuro-Oncology, 2017)
Molecular markers define the diagnosis of glioblastoma in the new WHO classification of 2016, challenging neuro-oncology centers to provide timely treatment initiation. The aim of this study was to determine whether a time delay to treatment initiation was accompanied by signs of early tumor progression in an MRI before the start of radiotherapy, and, if so, whether this influences the survival of glioblastoma patients. Images from 61 patients with early post-surgery MRI and a second MRI just before the start of radiotherapy were examined retrospectively for signs of early tumor progression. Survival information was analyzed using the Kaplan-Meier method, and a Cox multivariate analysis was performed to identify independent variables for survival prediction. 59 percent of patients showed signs of early tumor progression after a mean time of 24.1 days from the early post-surgery MRI to the start of radiotherapy. Compared to the group without signs of early tumor progression, which had a mean time of 23.3 days (p = 0.685, Student's t test), progression free survival was reduced from 320 to 185 days (HR 2.3; CI 95% 1.3-4.0; p = 0.0042, log-rank test) and overall survival from 778 to 329 days (HR 2.9; CI 95% 1.6-5.1; p = 0.0005). A multivariate Cox regression analysis revealed that the Karnofsky performance score, O-6-methylguanine-DNA-methyltransferase (MGMT) promoter methylation, and signs of early tumor progression are prognostic markers of overall survival. Early tumor progression at the start of radiotherapy is associated with a worse prognosis for glioblastoma patients. A standardized baseline MRI might allow for better patient stratification.
EVALuna2:22524

Erlangen Experience on radiosurgical Treatment for Trigeminal Neuralgia - Lettmaier, S.; Putz, Florian; Distel, Luitpold; Bischoff, B.; Bozhkov, Y.; Merkel, Andreas; Lambrecht, U.; Koca, S.; Fietkau, Rainer (2017)
EVALuna2:32886

Intraoperative Magnetic Resonance Imaging of Cerebral Oxygen Metabolism During Resection of Brain Lesions - Stadlbauer, Andreas; Merkel, Andreas; Zimmermann, Max; Sommer, Björn; Buchfelder, Michael; Meyer-Bäse, Anke; Rössler, Karl (World Neurosurgery, 2017)
OBJECTIVE: Tissue oxygen tension is an important parameter for brain tissue viability and its noninvasive intraoperative monitoring in the whole brain is of highly clinical relevance. The purpose of this study was the introduction of a multiparametric quantitative blood oxygenation dependent magnetic resonance imaging (MRI) approach for intraoperative examination of oxygen metabolism during the resection of brain lesions. METHODS: Sixteen patients suffering from brain lesions were examined intraoperatively twice (before craniotomy and after gross-total resection) via the quantitative blood oxygenation dependent technique and a 1.5-Tesla MRI scanner, which is installed in an operating room. The MRI protocol included T2*- and T2 mapping and dynamic susceptibility weighted perfusion. Data analysis was performed with a custom-made, in-house MatLab software for calculation of maps of oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO2) as well as of cerebral blood volume and cerebral blood flow. RESULTS: Perilesional edema showed a significant increase in both perfusion (cerebral blood volume +21%, cerebral blood flow +13%) and oxygen metabolism (OEF +32%, CMRO2 +16%) after resection of the lesions. In perilesional nonedematous tissue only, however, oxygen metabolism (OEF +19%, CMRO2 +11%) was significantly increased, but not perfusion. No changes were found in normal brain. Fortunately, no neurovascular adverse events were observed. CONCLUSIONS: This approach for intraoperative examination of oxygen metabolism in the whole brain is a new application of intraoperative MRI additionally to resection control (residual tumor detection) and updating of neuronavigation (brain shift detection). It may help to detect neurovascular adverse events early during surgery.
EVALuna2:102201

Intraoperative vascular DIVA surgery reveals angiogenic hotspots in tumor zones of malignant gliomas - Eyüpoglu, Ilker Yasin; Hore, Nirjhar; Fan, Zheng; Buslei, Rolf; Merkel, Andreas; Buchfelder, Michael; Savaskan, Nicolai E. (Scientific Reports, 2015)
Malignant gliomas belong to the most threatening tumor entities and are hallmarked by rapid proliferation, hypervascularization and an invasive growth pattern. The primary obstacle in surgical treatment lies in differentiation between healthy and pathological tissue at the tumor margins, where current visualization methods reach their limits. Here, we report on a novel technique (vascular dual intraoperative visualization approach - vDIVA) enabling visualization of different tumor zones (TZ I-III) on the basis of angiogenic hotspots. We investigated glioblastoma patients who underwent 5-ALA fluorescence-guided surgery with simultaneous intraoperative ICG fluorescence angiography. This vDIVA technique revealed hypervascularized areas which were further histologically investigated. Neuropathological assessments revealed tissue areas at the resection margins corresponding to TZ II, and postoperative CD34- and Map2 immunostaining confirmed these angiogenic hotspots to be occupied by glioma cells. Hence, the vascular architecture in this transitional zone could be well differentiated from both primary tumor bulk and healthy brain parenchyma. These data demonstrate that ICG fluorescence angiography improves state-of-the-art glioma surgery techniques and facilitates the future characterization of polyclonal attributes of malignant gliomas.
EVALuna2:7262

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

Study on the Impact of CMV-Encephalopathy on the Survival of Brain Cancer Patients Undergoing Radio(Chemo) therapy of the Brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, M. A.; Engelhorn, Tobias; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, F.; et al. (2017)
EVALuna2:32868

Supra-complete surgery via dual intraoperative visualization approach (DiVA) prolongs patient survival in glioblastoma - Eyüpoglu, Ilker Yasin; Hore, Nirjhar; Merkel, Andreas; Buslei, Rolf; Buchfelder, Michael; Savaskan, Nicolai (Oncotarget, 2016)
Safe and complete resection represents the first step in the treatment of glioblastomas and is mandatory in increasing the effectiveness of adjuvant therapy to prolong overall survival. With gross total resection currently limited in extent to MRI contrast enhancing areas, the extent to which supra-complete resection beyond obvious contrast enhancement could have impact on overall survival remains unclear. DiVA (dual intraoperative visualization approach) redefines gross total resection as currently accepted by enabling for the first time supra-complete surgery without compromising patient safety. This approach exploits the advantages of two already accepted surgical techniques combining intraoperative MRI with integrated functional neuronavigation and 5-ALA by integrating them into a single surgical approach. We investigated whether this technique has impact on overall outcome in GBM patients. 105 patients with GBM were included. We achieved complete resection with intraoperative MRI alone according to current best-practice in glioma surgery in 75 patients. 30 patients received surgery with supra-complete resection. The control arm showed a median life expectancy of 14 months, reflecting current standards-of-care and outcome. In contrast, patients receiving supra-complete surgery displayed significant increase in median survival time to 18.5 months with overall survival time correlating directly with extent of supra-complete resection. This extension of overall survival did not come at the cost of neurological deterioration. We show for the first time that supra-complete glioma surgery leads to significant prolongation of overall survival time in GBM patients.
EVALuna2:7326